Workers Willingness to Donate Human Biological Sample for Future Research in a South Western Nigerian Tertiary Health Center - BABATUNDE, Oluwole Adeyemi; ELEGBEDE, Olusegun Elijah; AYODELE, Lawrence Majekodunmi; FADARE, Joseph Olusesan; ATIBA, Adeniran Samuel; ISINKAYE, Ayodeji Olusola; OMEDE, Owen; OMONIJO, Adetunji (Journal of Asian Scientific Research, 2013)
Introduction: Human biological material is recognized as an important tool in research, and the demand for collections that combine samples and data is increasing. The aim of this study was to assess health workers knowledge of bio-banks, willingness to donate human biological samples, as well as their willingness to give consent for future use of their donated biological samples in research. Methodology: This is a cross-sectional descriptive study. The minimum sample size for this study was determined using the Fisher’s Formula. A sample size of 201 was derived and surveyed. . Proportional allocation of the sample sizes was done to the ten groups of staffs based on their population. Simple random sampling technique by balloting was used to select respondents in each group. The questionnaires were self-administered and the data generated were edited and validated manually for errors and entered into the computer for analysis using Epi-Info version 3.4.1. Results: Of all the respondents, 59.2%, 36% and 33.8% of respondents correctly identified Bio-banks’ capacity to store blood, semen and human tissues respectively. More than half of the respondents, 169 (54.3%), would give their consent for future use of their donated samples. 63.4% wanted the option of being able to withdraw their samples at any time while 59.2% stated that they would require a separate consent for each future use of donated samples. Conclusion: Health workers knowledge of bio-banks and willingness to donate human biologic sample was considerable despite its being a relatively new concept However most respondents expressed skepticism as regards willingness to give consent for future use of their donated biological samples in research. This study shows that this region is ready for research using Human Biological Samples provided more public enlightenment strategies are put in place.